OC-006 Setting up a centralised decontamination service: lessons learnt. (28th May 2012) - Jackson, V; Mitchell, J; Jones, D
Abstract : Introduction: Decontamination is moving towards a centralised service within secondary care. The aim of such is to maximise expertise and maintain quality standards. The development of centralised decontamination will minimise risk and assist the audit process. Within the authors workplace the decision was taken to house this service within the endoscopy department. Methods: An analysis of current services that used flexible endoscopes was undertaken including workforce, equipment and current usage of decontamination within the area it was undertaken. This included endoscopy, ENT & MFU outpatient and inpatient, ITU, Theatres. This led to a business case to request appropriate resource to enable implementation and deliver of required service for all users. Results: There was a difference in perceptions of a centralised decontamination service from all stakeholders. Each department had a tunnel vision with little regard for others. This led to a conflict due to all users having different priorities with little understanding of other pressures. Out of hours decontamination was an expectation from management with no acknowledgement of the impact this would have on the workforce. It was understood that all capital equipment would be pooled, however this was not accepted by some departments and led to shortages of endoscopes as services were reluctant to "share". The development of a band 4 decontamination supervisor helped the implementation of the service by offering expertise and leadership to all user groups. Management expectations of the service were often unrealistic due to lack of expertise in the area. The band 4 role offered a realistic solution using the knowledge and skills from their own experience in the field. Savings were delivered by the reduction of reprocessors required for maintenance contracts. Conclusion: Clear understanding of objectives is required prior to the development of any service. It is vital that a stakeholders group is formed and gives all involved the time to voice any concerns at any stage. Workforce requirements must be analysed to ensure the right skill mix is available to deliver the required knowledge and skills for implementation and sustainability. There needs to be greater emphasis on business continuity plans when cenralising any service. Competing interests: None declared.